Vocational identity, stress, coping, and social support as determinants of attrition, attendance, number of credits completed, and grades when returning to high school. - Schmidt, Douglas Derlin. (University of Ottawa (Canada), 2001)
The purpose of this dissertation is to review research on predictors of success when students return to high school, and to investigate the power of several risk and protective factors as predictors of success of students returning to school. Research findings regarding factors associated with initial departure from high school, returning to school, and repeated departure from high school are reviewed. Theories regarding departure from school are presented. A developmental psychopathology approach to predicting repeated departure from high school programs is presented which integrates cognitive, behavioural, social, and developmental theories. Findings are presented from a study on students returning to school who responded to questionnaires about demographics, vocational identity, stress level, coping style, and perceived social support. A total of 453 students participated who were returning to four types of academic environments: alternative outreach high schools (n = 267), a school for mothers (n = 46), a fourth year high school (n = 42), and college high school upgrading and completion programs (n = 98). The participants included 288 females (79 mothers and 209 nonmothers) and 165 males. The primary analyses were focused on how vocational identity, stress, coping behaviours, and social support predicted the outcome variables of attrition, attendance, number of credits completed, and grades at the end of the students' first 4 to 6 month term back in high school programs. Age, SES, and achievement were not found to be consistently predictive of outcomes. Males were more likely to leave school again, although no specific psychological variables were found to predict their departure. Females were found to be more likely to leave school again if they had a lower level of vocational identity, and if they had experienced a greater number of stressful life events in the year prior to returning to school. Gender, vocational identity, and life stress were not found to interact as moderators on outcomes. The results of this empirical study are believed to enrich theoretical understanding of success in returning to high school and will enable teachers and other professionals to more effectively evaluate and counsel students returning to school.
Keywords: Psychology, Clinical.